Предмет: Алгебра,
автор: oksanavinitska
40 баллов, если поможете!!!!!!!!!!!!!!!!!!
Превратите выражение в многочлен:
1) (4х^2 -х)3х
2) 4в^2-(а-2в)(а+2в)
3) -х^2-(х+4)(х-3)
Помогите! Срочно!
Ответы
Автор ответа:
0
1) (4x² - x) · 3x = 12x³ - 3x²
2) 4b² - [ a² - (2b)²] = 4b² - a² + 4b² = 8b² - a²
3) -x² - [ x² + 4x - 3x -12] = -x² -x² -x + 12 = -2x² - x + 12
2) 4b² - [ a² - (2b)²] = 4b² - a² + 4b² = 8b² - a²
3) -x² - [ x² + 4x - 3x -12] = -x² -x² -x + 12 = -2x² - x + 12
Похожие вопросы
Предмет: Математика,
автор: edalikim
Предмет: Обществознание,
автор: minxanovilya
Предмет: Другие предметы,
автор: Аноним
Предмет: Обществознание,
автор: bogdanova1204
Предмет: География,
автор: Вестар83